Incorporating a Pharmacist into the Discharge Process: A Unit-Based Transitions of Care Pilot. Issue 9 (October 2016) - Li, Hanlin; Guffey, William; Honeycutt, Laura; Pasquale, Timothy; Rozario, Nigel L.; Veverka, Angie
Objective: To evaluate the impact of a multifaceted, pharmacy-driven, unit-based transitions of care (TOC) program on all-cause 30-day readmission rates and to assess readmission rates in predefined subgroup patient populations. Methods: This prospective study included adult patients who were discharged from the pilot unit from January 5 to January 30, 2015. Patients who expired during hospitalization, left the hospital against medical advice, or transferred to another unit or nonaffiliated hospital were excluded. Possible pharmacist interventions included daily medication profile review, delivery of discharge medications to the bedside, counseling, and communication of a discharge medication list to follow-up providers. Patients had a 30-day follow-up period from the date of discharge to assess for readmission. Results: A total of 131 patients were screened and 94 patients were included. The primary outcome evaluating 30-day readmission rates occurred in 12.8% of patients in the pilot group versus 18.8% of patients in the historical control group ( p = .26). None of the patients who received all possible pharmacist interventions were readmitted. Secondary outcomes assessing readmission rates in predefined subgroup populations as well as length of stay were comparable between the 2 groups. All identified medication discrepancies were resolved prior to discharge. Conclusion: Readmission rates during the pilot were numerically lower but not statistically significant when compared with historical data. Enhancement of the pharmacy-driven TOC services through allocation of additional resources is in progress. Further investigation is warranted to determine the impact of a TOC pharmacist after the service is sustained.